Identification of nasopharyngeal microbial dysbiosis in COVID-19 patients by 16S rRNA gene sequencing - Kardaras, Filippos S.; Siatravani, Eirini; Tsilipounidaki, Katerina; Petinaki, Efthymia; Hatzigeorgiou, Artemis G.; Miriagou, Vivi (Frontiers in Microbiology, 2025)
BackgroundThe coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has prompted extensive research into factors influencing the onset and severity of the disease. Among these factors, the role of the nasopharyngeal microbiome, a vital ecosystem critical for respiratory health and immune modulation, remains incompletely understood. This study aimed to elucidate the relationship between the composition of nasopharyngeal microbiota and the clinical presentation of COVID-19 during the initial phase of infection.Materials and methodsA total of 81 nasopharyngeal swab samples were collected from individuals in Central Greece between January and February 2021. Following quality control, 77 samples were selected for microbiome analysis. This selection included SARS-CoV-2-negative controls (NE, n = 26) and SARS-CoV-2-positive patients classified as asymptomatic (AS, n = 19), mild (MI, n = 16), or severe (SE, n = 16) based on clinical criteria. All COVID-19-positive samples were collected within 2 days of symptom onset, and participants with recent hospitalization or antibiotic use were excluded. Microbiome profiling was performed using 16S rRNA gene-targeted metagenomic sequencing, followed by comprehensive bioinformatics and statistical analyses.ResultsSignificant differences were observed in both alpha and beta diversity measures, with alpha diversity decreasing as the severity of COVID-19 increased. Three of the four individual study groups, namely NE, MI, and SE, exhibited distinct microbial profiles, while the asymptomatic group showed greater heterogeneity. Significant variations in the abundance of specific phyla, families, and genera were identified between the different study groups. When comparing the NE and SE groups, we observed a significant increase in the abundance of the Proteobacteria phylum in the SE group, while the abundance of Fusobacteria was significantly lower in the SE group. In symptomatic COVID-19 patients, we observed a significant reduction in the abundance of key family constituents of the nasopharyngeal microbiota, such as Fusobacteriaceae, Prevotellaceae, and Streptococcaceae, suggesting a disruption in microbial homeostasis during the infection. Conversely, we found an increased prevalence of families associated with pathogenic or opportunistic pathogenic bacteria, including Enterobacteriaceae and Bacillaceae, in the SE group, suggesting a potential role of these taxa in the disease progression of COVID-19.ConclusionThese findings shed light on specific genera that undergo significant changes during COVID-19 infection and contribute to our understanding of the dynamic nature of the nasopharyngeal microbiome in relation to disease progression and severity.